2010
DOI: 10.1007/s10853-010-4973-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an AlN buffer layer and a thick-GaN layer grown on sapphire substrate by MOCVD

Abstract: An AlN buffer layer and a thick-GaN layer for high-electron-mobility transistors (HEMTs) were grown on sapphire substrate by metal-organic chemical vapor deposition (MOCVD). The structural and morphological properties of the layers were investigated by high resolution X-ray diffraction (HRXRD) and atomic force microscopy (AFM) techniques. The optical quality of the thick-GaN layer was also evaluated in detail by a photoluminescence (PL) measurement. It was found that the AlN buffer layer possesses high crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In this study, InGaN/GaN/AlN epilayers are grown on sapphire that results with high dislocation density. In order to see defects caused from crystallity level and mosaic block structure Dedge and Dscrew type dislocation densities may be calculated wih equations ( 1) and (2) [7][8][9]. Table 3 shows edge, screw type dislocation densities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, InGaN/GaN/AlN epilayers are grown on sapphire that results with high dislocation density. In order to see defects caused from crystallity level and mosaic block structure Dedge and Dscrew type dislocation densities may be calculated wih equations ( 1) and (2) [7][8][9]. Table 3 shows edge, screw type dislocation densities.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers studied for minimising defects of them [5,6]. For example, defect analysis, tilt and twist angles, dislocation density values of layers are determined by using symmetric and asymmetric peak broadening [7,8]. In general, it is sufficient to determine full width at half maximum (FWHM) of a symmetric plane reflection.…”
Section: Mosaic Defect and Afm Study On Gan/alinn/aln/sapphire Hemt Structures 1 Introductionmentioning
confidence: 99%
“…This is caused by inserting a LT AlN into the HT AlN layer, which prevents the propagation of cracks and defects from the first HT AlN layer to the top HT AlN layer . The top layer of the HLHT AlN buffer is formed with a high crystalline quality and a low defects density to promote the further growth of GaN . It has also been reported that intermediate temperature interlayer technique can markedly reduce the density of threading dislocations .…”
Section: Resultsmentioning
confidence: 99%
“…InGaN, GaN and AlGaN layers are grown on c-(001)-oriented sapphire substrate. Before the epitaxial growth operation, sapphire substrate is exposed to temperature of 1100 °C in nitrogen atmosphere for 10 min to remove the oxide layer on the surface of it [8,9]. Trimethylgallium (TMGa), trimethylaluminum (TMAl), trimethylindium (TMIn) and ammonia (NH 3 ) compound chemical reactions are gained from Ga, Al, In and N sources, respectively.…”
Section: Methodsmentioning
confidence: 99%